Analisis penerapan good corporate governance dalam meningkatkan kinerja karyawan di PT Pos Indonesia Kantor Cabang Utama Manado - Manggopa, Dian Ayu Merdekawati; Walandouw, Stanley Kho; Latjandu, Lady Diana (Riset Akuntansi dan Portofolio Investasi, 2025)
Good Corporate Governance is a set of principles that guarantee a company is run in a transparent, accountable, responsive, independent, and fair manner. Implementing Good Corporate Governance has a significant impact on various aspects of the organization, including employee performance. This research aims to analyse the relationship between the application of Good Corporate Governance and the improvement of employee performance. The study employs a qualitative method with a descriptive approach. Transparency in information and communication encourages employees to understand their roles, while accountability and result-based performance measurements create clear responsibilities. Accountability for tasks and the existence of reward and sanction systems maintain work discipline. Independence in decision-making and task completion provides employees with the freedom to innovate, while fair and objective treatment in career development motivates employees to contribute their best.